A comprehensive model-based index for identification of larval retention areas: A case study for Japanese anchovy Engraulis japonicus in the Yellow Sea. (September 2020) - Xing, Qinwang; Yu, Huaming; Yu, Haiqing; Sun, Peng; Liu, Yang; Ye, Zhenjiang; Li, Jianchao; Tian, Yongjun
Highlights: A comprehensive model-based index considering both retention rate and time to quantify larvae retention level was introduced and used to detect larval retention areas (LRA). Some prominent LRAs of Japanese anchovy in the Yellow Sea were identified. This approach can be widely applied to other pelagic species and in other continental shelf regions. Abstract: Larval retention has been recognized as a key factor/process affecting the recruitment of many pelagic fish species and detection of the larval retention areas (LRAs) is thus of crucial importance for studies of both recruitment dynamics and of fisheries management. However, most studies in relation to larval retention have adopted either retention rate or time to represent retention level. In this study, a newly developed approach based on a Lagrangian particle-tracking algorithm coupled with a hydrodynamic model, thereby jointly considering both retention rate and time to quantify larvae retention level, was introduced and used to identify the prominent LRAs for Japanese anchovy Engraulis japonicus in the Yellow Sea. Four prominent LRAs were identified, two of which locating in the Southern Yellow Sea match well with the aggregation of Japanese anchovy larvae found in previous field surveys. The spatial–temporal variation of instantaneous retention rate was further analyzed and the contribution rates of spawning grounds to LRAs as well as sensitivity of pelagic larval duration to the LRAs were investigated. Meanwhile, the LRAs defined in this study can be also used to explain the aggregations of microzooplankton and green algae in the southern part of the Yellow Sea. This approach can be widely applied to other pelagic species during their planktonic stages, which may further provide implications for studies on recruitment dynamics and on marine protected areas (MPAs) in the Yellow Sea as well as in other continental shelf regions containing abundant fishery resources.